Correlation of Facial Acupressure Knowledge With Massage Actions in Facial Treatment of Beauty and Cosmetics Study Program Students - Elvyra Yulia; Digna Ayuningtyas Chiquita; Patricia Sekarani (JURNAL PENDIDIKAN DAN KELUARGA, 2022)
This study aims to determine the relationship between knowledge of facial acupressure and massage in facial treatments for students of the cosmetology study program. This research was conducted at the private residence of dr. Elvyra Yulia, Sp.Ak. which is located at Jalan Cempaka Putih Tengah 22A No.9 Central Jakarta. The research method used is a descriptive quantitative method. The target population in this study were students of the cosmetology undergraduate study program who had studied facial care courses. The overall research sample was taken from as many as 30 students of the 2019 cosmetology undergraduate study program who had studied facial care courses. The instrument in this study uses a grid of instruments made based on indicators of the independent variable (X) namely facial acupressure knowledge with the dependent variable (Y) namely massage action in facial treatments. The questionnaire used in this study was a closed questionnaire. Analysis of the data used to determine the relationship between knowledge of facial acupressure and massage in facial treatments is the correlation technique Spearman Rank. This instrument uses a Likert scale. The instrument validity test was consulted with the r table and then tested for reliability. Based on the calculation of research data that the relationship between acupressure knowledge and massage facial treatment in the aspect of tofu reaches 85.2% which is in the very strong category, the application aspect is known to have a percentage of 78.0% which is in the strong category and the understanding aspect is 76, 5% are in a strong category. For the facial acupressure knowledge variable, it is known that the respondent's assessment is in the strong category with a percentage of 80.5%. In the aspect of facial acupressure, it is known to reach 81.9% which is in the very strong category. Based on the results of this study, it can be concluded that there is a positive and significant relationship between knowledge of acupressure and massage facials. This means that there is a strong relationship between knowledge of acupressure and massage facials.